ANALISIS RESEPSI REPRESENTASI PERPUSTAKAAN UGM PADA WEBSITE PERPUSTAKAAN - Fitri Handayani; Santana Sembiring (UIN Imam Bonjol Padang, 2021)
UGM library representation on the library website can be interpreted in a variety of ways by users depending on the user's information needs, experience and user background. This is an input for the library website to optimize the service and completeness of the information sources contained on the library website so that it can be interpreted easily and maximally by users.This study uses a qualitative approach with the reception analysis method. The informants selected in this study were 3 students from the third and fourth semesters. The results of this study indicate that: the library website contradicts the demands of the current library development that libraries have emphasized the function of social space rather than just as a source of information. The library website should also not be represented as a place for accessing limited information such as the ETD feature service which only contains abstracts / thesis titles, theses / dissertations only. Meanwhile, for online information retrieval, the library website can be used easily and can meet user information needs such as an online journal database to assist student assignments and theses. The results of this study, it can be concluded that the UGM library website makes it easy to access information sources and library services, it's just that sometimes the information presented cannot be easily understood and accessed in full text by users such as a collection of theses, theses, and dissertations..